The Supply Centers of the National Liberation Army in the Third Sector of the First Region, First Wilaya 1954 – 1962 (A Study of Models) - abdelaziz, hamza (The Algerian Historical Journal, 2026)
The third area (South Setif) of the third region of the first historical state played a significant role in the liberation revolution, aided by its strategic location that connects the first and third historical states. This is evident through the support of the local population for the revolution, their embrace of it, and their contributions to its success by establishing leadership for the National Liberation Army in various centers with different specializations. These centers played an important role in supplying the National Liberation Army, serving as the rear base for the armed struggle.